Environmental enteric dysfunction and growth - Mauro Batista de Morais; Giselia Alves Pontes da Silva (Brazilian Society of Pediatrics, 2019)
Objective: To describe the current indicators of environmental enteric dysfunction and its association with linear growth deficit and the height‐for‐age anthropometric indicator. Data sources: Narrative review with articles identified in PubMed and Scopus databases using combinations of the following words: environmental, enteric, dysfunction, enteropathy, and growth, as well as the authors' personal records. Data synthesis: In the last 15 years, new non‐invasive markers have been investigated to characterize environmental enteric dysfunction; however, the best tests to be used have not yet been identified. There is evidence that, in environmental enteric dysfunction, a systemic inflammatory process may also occur as a consequence of increased intestinal permeability, in addition to intestinal mucosa abnormalities. Bacterial overgrowth in the small intestine and changes in fecal microbiota profile have also been identified. There is evidence indicating that environmental enteric dysfunction can impair not only full growth but also the neuropsychomotor development and response to orally administered vaccines. It is important to emphasize that the environmental enteric dysfunction is not a justification for not carrying out vaccination, which must follow the regular schedule. Another aspect to emphasize is the greater risk for those children who had height impairment in early childhood, possibly associated with environmental enteric dysfunction, to present overweight and obesity in adulthood when exposed to a high calorie diet, which has been called "triple burden." Conclusions: According to the analyzed evidence, the control of environmental enteric dysfunction is very important for the full expression of growth, development, and vaccine response in the pediatric age group. Resumo: Objetivo: Descrever os indicadores atuais da disfunção entérica ambiental e sua relação com déficit de crescimento linear e com o indicador antropométrico estatura‐idade. Fontes dos dados: Revisão narrativa com artigos identificados no PubMed e Scopus com o uso de combinações das seguintes palavras: environmental, enteric, dysfunction, enteropathy e growth e dos arquivos pessoais dos autores. Síntese dos dados: Nos últimos 15 anos, vem sendo pesquisados novos marcadores não invasivos para caracterizar disfunção entérica ambiental. No entanto, ainda não foram identificados os melhores testes a serem usados. Existem evidências de que na disfunção entérica ambiental, além das anormalidades da mucosa intestinal, pode ocorrer também processo inflamatório sistêmico em consequência da maior permeabilidade intestinal. Sobrecrescimento bacteriano no intestino delgado e mudança no perfil da microbiota fecal também estão sendo identificados. Evidências indicam que a disfunção entérica ambiental pode comprometer não somente o pleno crescimento como também comprometer o desenvolvimento neuropsicomotor e a resposta de vacinas administradas por via oral. É importante destacar que a disfunção entérica ambiental não é justificativa para não fazer a vacinação, que deve seguir o calendário normal. Um outro aspecto a ser ressaltado é o risco maior dessas crianças que tiveram comprometimento da estatura na infância precoce, possivelmente associado à disfunção entérica ambiental, apresentarem na idade adulta excesso de peso e obesidade quando expostas a uma dieta rica em calorias, o que tem sido chamado "triple burden". Conclusões: De acordo com as evidências analisadas, o controle da disfunção entérica ambiental é muito importante para plena expressão do crescimento, desenvolvimento e resposta vacinal na faixa etária pediátrica. Keywords: Dysfunction, Enteric, Environmental, Enteropathy, Malnutrition, growth, Palavras‐chave: Disfunção, Entérica, Ambiental, Enteropatia, Desnutrição, crescimento